Effectiveness of “Heni’s Dental Flannel Book” On Improving Dental Health Care among Early Childhood - Nugraheni Widyastuti; Diyah Fatmasari; Masrifan Djamil (Alta Dharma Publisher, 2020)
One of the factors causing dental caries is the lack of children's knowledge resulting in a lack of awareness of children maintaining dental hygiene. To increase children's knowledge can promote dental health through child oral health education and mouth. The use of media is still less effective in health education that has been running. Therefore the need for innovation and development is to use media innovation